2016
DOI: 10.1002/smll.201502317
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hIAPP Amyloid Aggregation and Pancreatic β-Cell Toxicity by OH-Terminated PAMAM Dendrimer

Abstract: Human islet amyloid polypeptide (hIAPP, or amylin) forms amyloid deposits in the islets of Langerhans, a phenomenon that is associated with type-2 diabetes impacting millions of people worldwide. Accordingly, strategies against hIAPP aggregation are essential for the prevention and eventual treatment of the disease. Here, it is shown that generation-3 OH-terminated poly(amidoamine) dendrimer, a polymeric nanoparticle, can effectively halt the aggregation of hIAPP and shut down hIAPP toxicity in pancreatic MIN6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 79 publications
(93 reference statements)
2
110
0
Order By: Relevance
“…1013 For example, antiprion activity has been demonstrated by phosphorus dendrimers, maltose-based glycodendrimers (mPPI), poly(propyleneimine) PPI, and poly(ethylenimine) hyperbranched polymers. 1220 Of the myriad forms of polymeric NPs, hyperbranched polymers and dendrimers have demonstrated strong efficacies as antiamyloid agents, 11,12,15,2126 though anti-IAPP applications have only been explored recently. PPI glycodendrimers and lysine dendrimers have been investigated as anti-Aβ aggregation agents, 22,23 and hyperbranched PEG-based polymers with a dopamine moiety were found to be capable of inhibiting α-synuclein (αS) aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1013 For example, antiprion activity has been demonstrated by phosphorus dendrimers, maltose-based glycodendrimers (mPPI), poly(propyleneimine) PPI, and poly(ethylenimine) hyperbranched polymers. 1220 Of the myriad forms of polymeric NPs, hyperbranched polymers and dendrimers have demonstrated strong efficacies as antiamyloid agents, 11,12,15,2126 though anti-IAPP applications have only been explored recently. PPI glycodendrimers and lysine dendrimers have been investigated as anti-Aβ aggregation agents, 22,23 and hyperbranched PEG-based polymers with a dopamine moiety were found to be capable of inhibiting α-synuclein (αS) aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…11 Anionic low-generation dendrimers have been shown to modulate IAPP fibrillization and associated toxicity, 24 and inhibition of IAPP fibrillization and toxicity in vitro and ex vivo has recently been demonstrated by our team with OH-terminated polyamidoamine dendrimers (PAMAM-OH). 26 …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Among these, small organic molecules have received special interest because of their high permeability through the blood-brain barrier and potentially low cytotoxicity. 20 Several natural compounds have been found to prevent hIAPP brillization or to transform the mature brils into unstructured, off-pathway aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Further computational studies indicated that PAMAM dendrimers could encapsulate one or two hIAPP monomers within their core subsequently forming a unimolecular micelle that shielded amyloid contact from free hIAPP, thus terminating the amyloid fibrillization pathway. 53 …”
Section: Amyloid-mediated Cytotoxicity and Mitigation With Nanomaterialsmentioning
confidence: 99%
“…Chem. 2014; 289, 31066-31076 51 ; Nanoscale 2015, 7 , 18725–18737 52 ; Small , 2016, 12 , 1615–1626, 53 copyright 2016 John Wiley & Sons.…”
Section: Figurementioning
confidence: 99%